2022
DOI: 10.3389/fmed.2021.809270
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Progress in Nausea and Vomiting of Pregnancy and Hyperemesis Gravidarum: Challenges and Opportunities

Abstract: Nausea and vomiting of pregnancy (NVP) is a common condition that affects up to 70% of pregnant women. Hyperemesis gravidarum (HG) is considered the serious form of NVP, which is reported in 0.3–10.8% of pregnant women. NVP has a relatively benign course, but HG can be linked with some poor maternal, fetal, and offspring outcomes. The exact causes of NVP and HG are unknown, but various factors have been hypothesized to be associated with pathogenesis. With the advance of precision medicine and molecular biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
17

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 187 publications
(254 reference statements)
0
28
0
17
Order By: Relevance
“…Liu et al [ 13 ] stated in their study that not only hCG but also many different cytokines are secreted from trophoblasts in chorionic villi, and hCG alone may not be responsible for nausea and vomiting. For example, in a study by Fejzo M.S et al [ 14 ] it was found that the GDF-15 gene encodes a TGF-β superfamily member, which is expressed at high levels in the trophoblast cells of the placenta, and this protein, which has high levels in maternal blood especially in the first two trimesters, acts to facilitate placentation and suppress pro-inflammatory production of cytokines in order to suppress the continuation of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [ 13 ] stated in their study that not only hCG but also many different cytokines are secreted from trophoblasts in chorionic villi, and hCG alone may not be responsible for nausea and vomiting. For example, in a study by Fejzo M.S et al [ 14 ] it was found that the GDF-15 gene encodes a TGF-β superfamily member, which is expressed at high levels in the trophoblast cells of the placenta, and this protein, which has high levels in maternal blood especially in the first two trimesters, acts to facilitate placentation and suppress pro-inflammatory production of cytokines in order to suppress the continuation of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women who experience complaints of nausea and vomiting are natural symptoms that will be felt in the first trimester, usually, the mother will experience signs or symptoms such as dizziness, excessive salivation, and expelling some food and even everything that has been consumed. In addition, in many cases, pregnant women experience excessive nausea and vomiting which can worsen the general condition of the mother and can interfere with the daily activities of pregnant women (Dunbar et al, 2022;Liu et al, 2022). Nausea and vomiting in pregnancy can have serious consequences for the mother and especially the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54] Psychological symptoms such as anxiety and depression seem to be an outcome of the tension and the body burden of HG, rather than a reason. 55,56 Patients with HG were 5.5 and 6.7 times more vulnerable to fulfill the criteria for depression and anxiety disorder compared with comparative group, respectively. 57 To those with prolonged HG, several conditions including anxiety (32%) and PTSD (13%) were more likely to report.…”
Section: Hyperemesis Gravidarummentioning
confidence: 91%